VDC_100102372010.0X000001. Issue 1 (January 2018) - Postlewait, Lauren M.; Ethun, Cecilia G.; Mcinnis, Mia R.; Merchant, Nipun; Parikh, Alexander; Idrees, Kamran; Isom, Chelsea A.; Hawkins, William; Fields, Ryan C.; Strand, Matthew; Weber, Sharon M.; Cho, Clifford S.; et al.
Pancreatic mucinous cystic neoplasms (MCNs) are rare tumors typically of the distal pancreas that harbor malignant potential. Although resection is recommended, data are limited on optimal operative approaches to distal pancreatectomy for MCN. MCN resections (2000–2014; eight institutions) were included. Outcomes of minimally invasive and open MCN resections were compared. A total of 289 patients underwent distal pancreatectomy for MCN: 136(47%) minimally invasive and 153(53%) open. Minimally invasive procedures were associated with smaller MCN size (3.9 vs 6.8 cm; P = 0.001), lower operative blood loss (192 vs 392 mL; P = 0.001), and shorter hospital stay(5 vs 7 days; P = 0.001) compared with open. Despite higher American Society of Anesthesiologists class, hand-assisted (n = 46) had similar advantages as laparoscopic/robotic (n = 76). When comparing hand-assisted to open, although MCN size was slightly smaller (4.1 vs 6.8 cm; P = 0.001), specimen length, operative time, and nodal yield were identical. Similar to laparoscopic/robotic, hand-assisted had lower operative blood loss (161 vs 392 mL; P = 0.001) and shorter hospital stay (5 vs 7 days; P = 0.03) compared with open, without increased complications. Hand-assisted laparoscopic technique is a useful approach for MCN resection because specimen length, lymph node yield, operative time, and complication profiles are similar to open procedures, but it still offers the advantages of a minimally invasive approach. Hand-assisted laparoscopy should be considered as an alternative to open technique or as a successive step before converting from total laparoscopic to open distal pancreatectomy for MCN.